Cannabis use disorders may protect against certain disorders of the digestive organs in people with schizophrenia but not in healthy controls. Issue 3 (18th February 2020) - Olesen, Julie Aamand; Posselt, Christine Merrild; Poulsen, Chalotte Heinsvig; Nordentoft, Merete; Hjorthøj, Carsten
Abstract: Background. Previous studies have shown a potential for cannabis in disorders of the digestive organs. We aimed to investigate whether cannabis use disorders (CUD) would decrease the risk of incident disorders of the digestive organs, in people with schizophrenia and population controls. Methods. We combined nationwide Danish registers to identify 21 066 cases with schizophrenia and 176 935 sex-and-age-matched controls. Two models were analyzed for the associations between CUD and digestive disorders in time-varying Cox regressions: one adjusted for sex, year of birth, and calendar year; and one further adjusted for alcohol and other substance use disorders and parental education. Results. CUD was associated with a decreased risk of developing disorders of gut–brain interaction (e.g. irritable bowel syndrome, dyspepsia, etc.) among cases with schizophrenia (HR = 0.84, 95% CI 0.74–0.94, p = 0.003). CUD was associated with decreased risk of inflammatory bowel disease (HR = 0.70, 95% CI 0.49–0.99, p = 0.045) in the basically adjusted model, dropping just below statistical significance in the fully adjusted model (HR = 0.71, 95% CI 0.48–1.03, p = 0.07). CUD displayed a tendency toward a decreased risk of serious disorders of the digestive organs among cases with schizophrenia (HR = 0.89, 95% CI 0.77–1.02, p = 0.09) in the fully adjusted model. No associations were observed among controls. Conclusions. In people with schizophrenia, but not in controls, CUD is associated with decreased risk of disorders of gut–brain interaction and inflammatory bowel disease, and possibly other serious disorders of the digestive organs. Our findings could lead to new targets for treatment and prevention of disorders of the digestive organs.